A single-cell map of vascular and tissue lymphocytes identifies proliferative TCF-1+ human innate lymphoid cells - Gao, Yu; Alisjahbana, Arlisa; Boey, Daryl Zhong Hao; Mohammad, Imran; Sleiers, Natalie; Dahlin, Joakim S.; Willinger, Tim (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) play important roles in tissue homeostasis and host defense, but the proliferative properties and migratory behavior of especially human ILCs remain poorly understood. Here we mapped at single-cell resolution the spatial distribution of quiescent and proliferative human ILCs within the vascular versus tissue compartment. For this purpose, we employed MISTRG humanized mice as an in-vivo model to study human ILCs. We uncovered subset-specific differences in the proliferative status between vascular and tissue ILCs within lymphoid and non-lymphoid organs. We also identified CD117-CRTH2-CD45RA+ ILCs in the spleen that were highly proliferative and expressed the transcription factor TCF-1. These proliferative ILCs were present during the neonatal period in human blood and emerged early during population of the human ILC compartment in MISTRG mice transplanted with human hematopoietic stem and progenitor cells (HSPCs). Single-cell RNA-sequencing combined with intravascular cell labeling suggested that proliferative ILCs actively migrated from the local vasculature into the spleen tissue. Collectively, our comprehensive map reveals the proliferative topography of human ILCs, linking cell migration and spatial compartmentalization with cell division.